ISLAMIC FINANCIAL DEVELOPMENT AND INCOME INEQUALITY IN INDONESIA - Azwar, Azwar; Possumah, Bayu Taufiq; Aqbar, Khaerul (UNISSULA, 2022)
The objective of this paper is to analyze the short and long run relationship between Islamic financial development and income inequality in Indonesia over the period of 2000-2020. The study has employed the Auto Regressive Distributed Lag (ARDL) bound testing approach and the Error Correction Mechanism (ECM) to examine the existence of long-run and short-run relationship, while variance decomposition (VDC) technique is used to provide Granger causal relationship between the variables. The cointegration tests show that there is a long run relationship between Islamic financial development, economic growth, inflation and income inequality in Indonesia. However, Islamic financial development itself is found to be not statistically significant in influencing income inequality during the sample period for long-run. This study found a positive and statistically significant (10%) effect of Islamic financial development in explaining the changes in income inequality in the short run. In terms of policy, enhancing financial access is needed to ensure that financial development fully supports the reduction of income inequality in Indonesia.